Dakwah Digital: Mengukur Dampak dan Efektivitas Kampanye Dakwah Online terhadap Audiens Muda: Digital Da'wah: Measuring the Impact and Effectiveness of Online Da'wah Campaigns on Young Audiences - Fathul Amin; Agus Ali Sururi (CV Omah Kreator, 2025)
This study examines the impact and effectiveness of digital da'wah on young audiences using both quantitative and qualitative methods. Data was collected from 300 respondents aged 18–30 who actively engage with religious content on YouTube, Instagram, and TikTok. The survey results show that 72% of respondents access digital da'wah more than three times a week, with 85% preferring short and visually engaging content. Additionally, 78% favor topics related to daily life, such as social media, careers, and interpersonal relationships. Statistical analysis reveals a significant positive correlation (r = 0.68, p < 0.01) between the frequency of digital da'wah consumption and increased religious knowledge. However, only 52% of respondents report significant behavioral changes. Furthermore, 45% feel confused by the diversity of religious interpretations in digital da'wah content. Interviews with 20 participants provide deeper insights, showing that while many feel more connected to their faith through interactive content, some find the messages lacking depth or misaligned with their understanding of Islamic teachings. In conclusion, digital da'wah effectively enhances religious knowledge, but its impact on behavioral change remains limited. This study highlights the need for engaging and contextually relevant content, along with careful curation and guidance to help audiences navigate diverse religious interpretations.